A modified knowledge-based filtering method that uses case-based reasoning applied in real-estate recommendation system - Ronquillo, Lance Gerard V, Villa Gabriel C. 4 0 16; 5 (2023)
u
Undergraduate Thesis: (Bachelor of Science in Information Technology), Pamantasan ng Lungsod ng Maynila, 2023.
Keywords: 2 -- 0; 6; 20; 20; 2